Does a Crisis Change News Habits? A Comparative Study of the Effects of COVID-19 on News Media Use in 17 European Countries. Issue 9 (21st October 2021) - Van Aelst, Peter; Toth, Fanni; Castro, Laia; Štětka, Václav; Vreese, Claes de; Aalberg, Toril; Cardenal, Ana Sofia; Corbu, Nicoleta; Esser, Frank; Hopmann, David Nicolas; Koc-Michalska, Karolina; Matthes, Jörg; et al.
Abstract: Exogenous shocks like the COVID-19 pandemic unleashes multiple fundamental questions about society beyond public health. Based on the classical concept of 'need for orientation' and the literature on the role of the media in times of crisis, we investigate to what extent the COVID-19 pandemic affected news consumption in comparative perspective. Based on a two-wave panel survey in 17 mostly European countries, our study targets the role of both legacy news brands (TV, radio, newspapers) and so-called contemporary news media (Internet-based and social media) during this global health crisis. Our results show an overall rise of news use across countries, but only for some types of news media. We find an increase of TV news consumption, and a higher reliance on social media and the Internet for news and information. This indicates that in times of crises and an unusually strong need for orientation, people mainly turn to news sources that are easily available and offer a more immediate coverage. Furthermore, we find the rise in news use to be mainly present among those who already have a higher level of trust in legacy media and among people that were more concerned about the impact of the pandemic.